Rationale and design of Treatment of Acute Ischaemic Stroke with Edaravone Dexborneol II (TASTE-2): a multicentre randomised controlled trial - Anding Xu; Yongjun Wang; Feng Wang; Qiang Dong; Chunjuan Wang; Yi Yang; Ning Wang; Hong-Qiu Gu (Stroke and Vascular Neurology)
Background Edaravone dexborneol is believed to be a novel cytoprotective drug, demonstrating a synergistic combination of antioxidative and anti-inflammatory properties in animal models. The Treatment of Acute Ischaemic Stroke with Edaravone Dexborneol (TASTE) trial demonstrated its superior efficacy over edaravone alone for acute ischaemic stroke (AIS) patients. However, its efficacy in individuals undergoing endovascular therapy (EVT) remains uncertain.Aim To clarify the rationale and design of the TASTE II (TASTE-2) trial.Design The TASTE-2 is a multicentre, double-blind, randomised, placebo-controlled trial designed to evaluate the efficacy and safety of edaravone dexborneol in patients with AIS and large-vessel occlusion in the anterior circulation. The eligible participants, presenting with a National Institute of Health Stroke Scale score between 6 and 25 (range 0–42, with larger values suggesting severe neurological dysfunction) and an Alberta Stroke Program Early Computed Tomography Score ranging from 6 to 10 (range 0–10, with smaller values suggesting larger infarction) within the initial 24 hours after symptom onset, will be randomly allocated to either the edaravone dexborneol group or the placebo group in equal proportions prior to thrombectomy. The treatment will be continuously administered for a duration of 10–14 days. A follow-up period of 90 days will be implemented for all participants.Study outcomes The primary efficacy outcome is defined as achieving favourable functional independence, measured by a modified Rankin Scale of 0–2 at 90 days. The primary safety outcome focuses on the incidence of serious adverse events.Discussion The TASTE-2 trial will provide evidence to determine whether the administration of edaravone dexborneol in AIS patients undergoing EVT could yield significant improvements in neurological function.